Ras-Related C3 Botulinum Toxin Substrate 1 Combining With the Mixed Lineage Kinase 3- Mitogen-Activated Protein Kinase 7- c-Jun N-Terminal Kinase Signaling Module Accelerates Diabetic Nephropathy - Changjiang Ying; Jiao Dai; Gaoxia Fan; Zhongyuan Zhou; Tian Gan; Yusheng Zhang; Yuanjian Song; Xiaoyan Zhou (Frontiers in Physiology, 2021)
Ras-related C3 botulinum toxin substrate 1 (RAC1) activation plays a vital role in diabetic nephropathy (DN), but the exact mechanism remains unclear. In this study, we attempted to elucidate the precise mechanism of how RAC1 aggravates DN through cellular and animal experiments. In this study, DN was induced in mice by intraperitoneal injection of streptozotocin (STZ, 150mg/kg), and the RAC1 inhibitor NSC23766 was administered by tail vein injection. Biochemical indicators, cell proliferation and apoptosis, and morphological changes in the kidney were detected. The expression of phosphorylated c-Jun N-terminal kinase (p-JNK), nuclear factor-κB (NF-κB), and cleaved caspase-3 and the interaction between RAC1 and the mixed lineage kinase 3 (MLK3)-mitogen-activated protein kinase 7 (MKK7)-JNK signaling module were determined. Furthermore, the colocalization and direct co-interaction of RAC1 and MLK3 were confirmed. Our results showed that RAC1 accelerates renal damage and increases the expression of p-JNK, NF-κB, and cleaved caspase-3. However, inhibition of RAC1 ameliorated DN by downregulating p-JNK, NF-κB, and cleaved caspase-3. Also, RAC1 promoted the assembly of MLK3-MKK7-JNK, and NSC23766 blocked the interaction between RAC1 and MLK3-MKK7-JNK and inhibited the assembly of the MLK3-MKK7-JNK signaling module. Furthermore, RAC1 was combined with MLK3 directly, but the RAC1 Y40C mutant inhibited the interaction between RAC1 and MLK3. We demonstrated that RAC1 combining with MLK3 activates the MLK3-MKK7-JNK signaling module, accelerating DN occurrence and development, and RAC1 Y40 is an important site for binding of RAC1 to MLK3. This study illustrates the cellular and molecular mechanisms of how RAC1 accelerates DN and provides evidence of DN-targeted therapy.